Distribution, Sources, and Biogeochemistry of Carbon Pools (DIC, DOC, and POC) in the Mangrove-Fringed Zhangjiang Estuary, China - Yan, Ran; Feng, Jianxiang; Wang, Yuming; Fu, Linxi; Luo, Xiangxin; Niu, Lixia; Yang, Qingshu (Frontiers in Marine Science, 2022)
The lateral carbon export related to mangroves is of great scientific significance and ecological value in the global carbon cycle. The dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), particulate organic carbon (POC), and stable isotopes (δ13POC) of water samples were quantified in the flood (September 2020) and dry (January 2021) seasons in Zhangjiang Estuary. The results revealed that the carbon compositions in the tidal channel of the Zhangjiang Estuary are as follows: DIC = 20.3 mg/L (70%), DOC = 5.0 mg/L (21%), and POC = 2.6 mg/L (9%) in the flood season. The contents of all carbon compositions were significantly larger in the flood season than in the dry season (P < 0.05). Spatially, the DIC and DOC exhibited similar characteristics. Owing to the higher mineralization and leaching in the flood season, the pore water and groundwater played an important role in the carbon outwelling, and they formed a hotspot with high values. While, in the dry season, DIC and DOC formed local carbon sinks under the influence of mariculture and the Beijiang sluice. There was no spatial difference in the POC, which may have been due to the resuspension of the sediments and the limited sand transport. The MixSIAR model indicates that the source of the POC is overwhelmingly the mariculture, accounting for 70.2% in the form of microalgae, followed by the mangrove, accounting for 10.2–52.2%, which indicates that the mangrove outwelling in the Zhangjiang Estuary is relatively conservative. If mariculture is prohibited, the mangrove will become the natural contributor. The DIC-δ13POC and DOC-POC relationships represent the biogeochemical process of microbial photosynthesis and the physical process of adsorption-desorption of organic carbon by redundancy analysis, respectively. This initial dataset for this region should be included in other studies to improve the mangrove outwelling estimate.